Peripheral blood examination to assess bleeding risk in children with dengue infections - Irene Huwae; Kurniawan Kadafi (Indonesian Pediatric Society, 2012)
Background Dengue viral infection may cause mild to severeclinical manifestations, with or without bleeding. A number offactors may cause bleeding in patients with dengue. However,health providers may be unable to perform the examinationsrequired to sufficiently predict the risk of bleeding.Objective To find risk factors for bleeding using peripheral bloodexaminations in children with dengue infection.Methods This crossô€sectional study was conducted at thePediatric Ward of the Dr. Saiful Anwar General Hospital,Malang, from January 2010 to December 2011. We includedchildren aged 1 to 18 years with dengue viral infection, asconfirmed by the 1997 WHO criteria and serology. Peripheralblood examinations were made daily, depending on the patient'scondition. We classified the bleeding status into nonô€bleeding,petechial bleeding (mild hemorrhage), and mucosal bleeding(severe hemorrhage). We recorded subjects' bleeding status atthe time of their highest packed cell volume (PCV), and recordedtheir leukocyte and platelet counts at that time. We computedthe parameters' medians and compared them to bleeding statusby Chiô€square test. For significant (P<0.05) associations wecalculated the OR (odds ratio) lith a 95% confidence interval.All patients were treated according to the 1997 WHO dengueguidelines.Results There were all 294 subjects with dengue and 282subjects had complete data, 202 lith bleeding (120 petechial,82 mucosal bleeding) and 80 without bleeding. The medianPCV was 36.8%, while median platelet count was 51,000/,uLand median leukocyte count was 3,400/,uL. The OR of PCV> 36.8% for bleeding was 2.31 (95%CI 1.35 to 3.95). The ORof platelet count <51,000/ ,uL for bleeding was 2.34 (95%CI1.37 to 3.99) compared to platelet count> 51,000/ ,uL. TheOR of platelet count < 51,000/ ,uL for mucosal bleeding was3.39 (95%CI 1.78 to 6.48). Chiô€square analysis for leukocytecount showed it was not associated with bleeding in dengue(Pô€‘ 0.186).Conclusion The PCV level > 36.8% increased the risk forbleeding by 2.31 times, for both petechial and mucosal bleeding.Platelet count < 51,000/ ,uL increased the risk for bleeding 2.34times and for mucosal bleeding by 3.4 times. Leukocytes countwas not associated with bleeding. Basic laboratory examinationsof PCV and platelet count may, therefore, be used as a predictorof bleeding in children with dengue infection. [paediatr lndones.2012;52:175-80].